Jawāhir-i tafsīr Tafsīrī adabī ʿirfānī ḥurūfī, shāmil-i muqaddamaʾī dar ʿulūm-i Qurʾānī wa tafsīr-i sūra-yi ḥamd - Kāshifī, Wāʿiẓ (Persian E-Books Miras Maktoob, 2000)
The Qurʾān is a complex text, and it has been regarded as such since the very beginning. Qurʾān interpretation or tafsīr was already practiced by the Prophet's nephew ʿAbdallāh born al-ʿAbbās, who used folklore and poetry to interpret his uncle's revelations. With the passing of time, Qurʾānic exegesis developed from a mere branch of tradition ( ḥadīth ) into a full-fledged, independent discipline. The earliest Persian Qurʾān commentary was a translation of Abū Jaʿfar al-Ṭabarī's (d. 311/923) Jāmiʿ al-bayān ʿan taʾwīl āy al-Qurʾān , made in 345/956. The Persian commentary contained in the present volume was composed in 890/1485 in Herat by Wāʿiẓ Kāshifī (d. 910/1504-05), a prolific author, preacher and mystic of the Timurid era. Originally meant to comprise four volumes, it was discontinued halfway the fourth sura, and is only partially reproduced in the present edition. Kāshifī's detailed, literary commentary stands out by his unique use of the esoteric properties of letters and numbers